2017
DOI: 10.1093/mnras/stx2614
|View full text |Cite
|
Sign up to set email alerts
|

Tidal interaction, star formation and chemical evolution in blue compact dwarf galaxy Mrk 22

Abstract: The optical spectroscopic and radio interferometric HI 21 cm-line observations of the blue compact dwarf galaxy Mrk 22 are presented. The Wolf-Rayet (WR) emission line features corresponding to high ionization lines of HeII λ4686 and CIV λ5808 from young massive stars are detected. The ages of two prominent star forming regions in the galaxy are estimated as ∼10 Myr and ∼ 4 Myr. The galaxy has non-thermal radio deficiency, which also indicates a young star-burst and lack of supernovae events from the current s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 172 publications
(225 reference statements)
2
5
0
Order By: Relevance
“…The higher electron density, particularly in the density-bounded HII region, is consistent with typical electron density obtained in prior low-redshift LyC/Lyα leakers such as GPs (e.g., Izotov et al 2020a;Guseva et al 2020). In the ionization-bounded HII region (i.e., extended disk outside the circle), it is typical ( 100 cm −3 ), comparable to that observed in normal starforming galaxies (e.g., Guseva et al 2011;Izotov & Thuan 2011;Paswan et al 2018Paswan et al , 2019.…”
Section: Wolf-rayet Feature and Physical Conditions Of Ionized Gassupporting
confidence: 52%
See 1 more Smart Citation
“…The higher electron density, particularly in the density-bounded HII region, is consistent with typical electron density obtained in prior low-redshift LyC/Lyα leakers such as GPs (e.g., Izotov et al 2020a;Guseva et al 2020). In the ionization-bounded HII region (i.e., extended disk outside the circle), it is typical ( 100 cm −3 ), comparable to that observed in normal starforming galaxies (e.g., Guseva et al 2011;Izotov & Thuan 2011;Paswan et al 2018Paswan et al , 2019.…”
Section: Wolf-rayet Feature and Physical Conditions Of Ionized Gassupporting
confidence: 52%
“…For some spaxels, the line flux ratios of f Hα /f Hβ are found to be below the expected theoretical value of 2.86. A low value of f Hα /f Hβ is often associated with intrinsically low reddening, and hence we assumed an internal E(B − V ) values as zero for such cases (e.g., Paswan et al 2018Paswan et al , 2019. Throughout this work, we have used only those emission lines whose signal-to-noise ratio (SNR) is 3.…”
Section: Datamentioning
confidence: 99%
“…A low value of f Hα /f Hβ is often associated with intrinsically low reddening and hence we assumed a E(B -V) internal as zero for such cases. Previously, lower than theoretical value of f Hα /f Hβ has been reported in several galaxies (López-Sánchez & Esteban 2009;Ramya et al 2009;Gunawardhana et al 2013;Paswan et al 2018). Such low value is usually believed as resulted from variations in physical conditions of ionized gas such as high electron temperature or low electron density in the emission region for which the theoretical ratio f Hα /f Hβ may be less than 2.86 (e.g., Grinin 1980;López-Sánchez & Esteban 2009).…”
Section: Results and Analysismentioning
confidence: 92%
“…Alternatively, it could be a merger system as double nuclei is indicated (Mazzarella et al 1991). Paswan et al (2018) recently found a significant metallicity difference between the two nuclei, which also suggests that MRK 22 could be a merging system of two galaxies.…”
Section: Mrk 22mentioning
confidence: 96%